Research progress in antibacterial modification of titanium implant surface - Yong-Han WEI; Yu-Jie SHI; Wan-Qi PENG; Wen-Zhong XIE; Ling-Ling ZHANG; Jun SHAO (Yixue xinzhi zazhi)
Pure titanium and its alloys with good mechanical strength and biocompatibility, are currently one of the commonly used permanent implants in clinical practice. However, the related in-fection caused by microorganisms will lead to the tissue around the titanium implant produce in-flammatory reactions, which may bring the risk of secondary operation for patients. The formation of bacterial biofilm on the surface of titanium implants, including the adhesion, reconstruction and mat-uration of bacterial colonies, is one of the main reasons of infection. Therefore, modifying the surface of titanium implants to inhibit the formation of bacterial biofilm is one of the effective ways to reduce postoperative infection caused by titanium implants. This method has attracted great interests in the field of orthopedics and dental implants. This paper first introduces the process of bacteria adhesion and maturation on the surface of implants, then summarizes the methods about surface modification and antibacterial mechanism of pure titanium and titanium alloy in detail. Finally, combining with the problems that haven’t been solved in the clinic anti-infection methods, the future development trend of titanium implants is discussed.